Synthesis of dental matrix proteins and viability of odontoblast-like cells irradiated with blue LED - Alonso, Juliana Rosa Luiz [UNESP] (2016)
To evaluate the effect of irradiation with light-emitting diode (LED; 455 nm) on the viability and synthesis of dentin matrix proteins by odontoblast-like cells, MDPC-23 cells were cultivated (104 cells/cm2) in 24-well culture plates. After 12 h incubation in Dulbecco’s modified Eagle’s medium (DMEM), the cells were submitted to nutritional restriction by means of reducing the concentration of fetal bovine serum (FBS) for an additional 12 h. Cells were irradiated one single time with one of the following energy densities (EDs): 0.5, 2, 4, 10, or 15 J/cm2 and irradiance fixed at 20 mW/cm2. Non-irradiated cells served as control. After 72 h, cells were evaluated with regard to viability (methylthiazol tetrazolium technique (MTT)), mineralization nodule (MN) formation, total protein (TP) production, alkaline phosphatase activity (ALP), and collagen synthesis (Sircol), n = 8. The data were submitted to Kruskal–Wallis and Mann–Whitney tests (p > 0.05). There was no statistical difference between the viability of cells irradiated or not (control), for all the EDs. However, an increase in TP was observed for all the EDs when compared with the control group. A reduced ALP activity was seen in all irradiated groups, except for the ED of 0.5 J/cm2, which did not differ from the control. There was no difference between the irradiated groups and control regarding collagen synthesis, with the exception of the ED of 10 J/cm2, which inhibited this cell function. Significant reduction in MN occurred only for the EDs of 0.5 and 2 J/cm2. The single irradiation with blue LED (455 nm), irradiance of 20 mW/cm2, and energy densities ranging from 0.5 to 15 J/cm2 exerted no effective biostimulatory capacity on odontoblast-like cells.